Comparative Costs and Returns Pattern of Small-scale Groundnut Milling of RMP-12 and Ex-dakar Varieties in Gombe Metropolis, Gombe State Nigeria - Abdullahi Saleh; Ochi J. E.; Mohammed Sani Hussain (Jurnal Ekonomi dan Studi Pembangunan, 2018)
The study determined the costs and returns involved in small-scale groundnut oil processing of two varieties in Gombe metropolis. Twelve markets were purposively selected for their popularity in groundnut oil processing, where 90 processors were selected by simple random sampling technique. Data were collected using structured questionnaires and were analysed using farm budget model, profitability index and t-test analysis. The results revealed that Cost of shelled groundnut constituted the major (92.3% and 91.6%) components of processing costs (P<0.01) for RMP-12 and Ex-dakar respectively. The  gross ratios, fixed ratios and operating ratios of the two groundnut varieties were < 1, meaning that the business was profitable. Also, the returns per naira invested of the respective groundnut varieties was ₦ 0.17 ($ 0.0006) and ₦ 0.25 ($ 0.0009) significant (P<0.01). Although, the RMP-12 variety gave higher gross income, but the Ex-dakar variety gave higher profit of ₦ 7,428.80 ($ 26.20) per tonne per week (P<0.01). To achieve higher profit, the traders should embark on Ex-dakar variety as the main resource input. They should also have access to formal loans so as to improve productivity and efficiency. Keywords: Comparative costs, Groundnut, Small-scaleJEL Classification: D24; D61